Antibacterial activity of plant-extract mediated silver nanoparticles against Klebsiella spp. in Africa: a systematic review - Dunah, Marcus Barlay; Abdalla, Mai Ali; Wawata, Ibrahim G.; Adekilekun, Tijani Naheem (Frontiers in Microbiology, 2026)
IntroductionAntimicrobial resistance (AMR) among Klebsiella spp. is an escalating global health concern, particularly in resource-limited settings. The rapid spread of multidrug-resistant strains has rendered conventional antibiotics increasingly ineffective. In Africa, the green synthesis of silver nanoparticles (AgNPs) using medicinal plant extracts offers a sustainable and cost-effective approach for developing novel antibacterial agents.MethodsThis systematic review followed PRISMA 2020 guidelines. A comprehensive search was conducted across PubMed, Scopus, Web of Science, Google Scholar, and African Journals Online (AJOL) for studies published between January 2015 and May 2025. Eligible studies included in vitro experiments evaluating the antibacterial activity of plant extract–mediated AgNPs against Klebsiella spp. Two reviewers independently screened articles, extracted data, and assessed quality using the Joanna Briggs Institute (JBI) Critical Appraisal Checklist for in vitro studies.ResultsOut of 323 identified records, 14 studies met the inclusion criteria. The studies originated from Egypt (n = 4), Nigeria (n = 4), Kenya (n = 3), South Africa (n = 2), Tunisia (n = 1), and Ghana (n = 1). Frequently used plant species included Azadirachta indica, Moringa oleifera, Vernonia amygdalina, Allium sativum, Carica papaya, and Ocimum gratissimum. Silver nanoparticles synthesized from these extracts were typically spherical and measured 20–100 nm in diameter. All studies reported significant in vitro antibacterial activity, with zones of inhibition ranging from 10 to 24 mm and minimum inhibitory concentrations (MICs) ranging from 6.25 to 50 μg/mL.ConclusionPlant-mediated silver nanoparticles exhibit strong in vitro efficacy against Klebsiella spp., supporting their potential role as alternative or adjunct antimicrobial agents in managing AMR. However, further in vivo studies, toxicological assessments, and standardization of nanoparticle synthesis and testing protocols are essential for their translation into clinical application.